STABILITY AND ADAPTABILITY IN TESTS OF PROGENIES OF MYRACRODRUON URUNDEUVA UNDER FOUR SYSTEMS OF PLANTATION - Oliveira Canuto, Daniela Silvia de [UNESP]; Silva, Alexander Marques da [UNESP]; Teixeira de Moraes, Mario Luiz [UNESP]; Vilela de Resende, Marcos Deon (Univ Federal Lavras-ufla, 2016)
The species Myracrodruon urundeuva, or aroeira, possesses resistant wood, but of slow growth, so it is advisable its plantation with other species as an alternative of income until its complete development. This work had the objective to evaluate the stability and adaptability in four progeny tests of Myracrodruon urundeuva under different plantation forms: associated with arboreal essences (TP-1), homogeneous (TP-2), agroforestry systems (AFS) with annual cultures (TP-3) and AFS with eucalyptus (TP-4), installed in 1997 at Fazenda de Pesquisa, Extensao e Ensino of UNESP campus Ilha Solteira - SP, in Selviria - MS. Seeds were collected from 30 main trees located in the Estacao Ecologica de Paulo de Faria - SP. Total height (m), diameter at breast height DBH (cm), and stem form were evaluated up to ten years of age. Randomized complete blocks design was used. The software SELEGEN was used for the estimates of variance components, genetic parameters and stability and adaptability (MHPRVG). Aroeira had better height in the TP-3, DBH in the TP-2 and similar stem form in all four TP. The genetic parameters indicated that DBH possesses the largest control and genetic variation and correlation genotype and environment. The simultaneous selection presented the best progenies, identical to the progenies from the selection of MHPRVG, which indicates this is a refined method of selection.
Keywords: Aroeira; Genotype x environment interaction; Agroforestry system